The serological diversity of serum IgG/IgA/IgM against SARS‐CoV‐2 nucleoprotein, spike, and receptor‐binding domain and neutralizing antibodies in patients with COVID‐19 in Japan. Issue 3 (13th April 2022) - Kaneko, Yudai; Sugiyama, Akira; Tanaka, Toshiya; Fukui, Kazushige; Taguchi, Akashi; Tatsuno, Kenji; Nakayama, Aya; Koga, Kazumasa; Kishi, Yoshiro; Daming, Wang; Qian, Chungen; Xia, Fuzhen; et al.
Abstract: Background: We compared the temporal changes of immunoglobulin M (IgM), IgG, and IgA antibodies against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) nucleoprotein (N), spike 1 subunit (S1), and receptor‐binding domain (RBD), and neutralizing antibodies (NAbs) against SARS‐CoV‐2 in patients with coronavirus disease 2019 (COVID‐19) to understand the humoral immunity in COVID‐19 patients for developing drugs and vaccines for COVID‐19. Methods: A total of five confirmed COVID‐19 cases in Nissan Tamagawa Hospital in early August 2020 were recruited in this study. Using a fully automated chemiluminescence immunoassay analyzer, we measured the levels of IgG, IgA, and IgM against SARS‐CoV‐2 N, S1, and RBD and NAbs against SARS‐CoV‐2 in COVID‐19 patients' sera acquired multiple times in individuals from 0 to 76 days after symptom onset. Results: IgG levels against SARS‐CoV‐2 structural proteins increased over time in all cases but IgM and IgA levels against SARS‐CoV‐2 showed different increasing trends among individuals in the early stage. In particular, we observed IgA increasing before IgG and IgM in some cases. The NAb levels were more than cut‐off value in 4/5 COVID‐19 patients some of whose antibodies against RBD did not exceed the cut‐off value in the early stage. Furthermore, NAb levels against SARS‐CoV‐2 increased and kept above cut‐off value more than around 70 days after symptom onset in all cases. Conclusion: Our findings indicate COVID‐19 patients should be examined for IgG, IgA, and IgM against SARS‐CoV‐2 structural proteins and NAbs against SARS‐CoV‐2 to analyze the diversity of patients' immune mechanisms.